PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PERAWAT RUMAH SAKIT SYAFIRA PEKANBARU - Oldemar "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to determine the effect of work environment on job satisfaction of nurses in Syafira Hospital Pekanbaru. Work environment as an independent variable (X) has been formulated by the company that physical work environment and Non-physical work environment. While job satisfaction as the dependent variable (Y). study was conducted on nurses in Syafira Hospital Pekanbaru by 63 people.Data obtained from the questionnaire and further processed and then tested using statistical analysis such as simple regression analysis , t test, correlation analysis and determination using SPSS program.The results showed that the test results of hypothesis testing. tcount(7,750) >ttable (2,000). This suggest that the work environment affect the level of job satisfaction. The magnitude of the influence of environment on job satisfaction of nurses in Syafira Hospital Pekanbaru is 49,6%.Keyword : physical work environment,Non-physical work environment and Job satisfaction.